2005
DOI: 10.1242/jcs.02644
|View full text |Cite
|
Sign up to set email alerts
|

Oocytes prevent cumulus cell apoptosis by maintaining a morphogenic paracrine gradient of bone morphogenetic proteins

Abstract: Paracrine factors secreted by the oocyte regulate a broad range of cumulus cell functions. Characteristically, cumulus cells have a low incidence of apoptosis and we proposed that this is due to oocyte-secreted factors acting in an anti-apoptotic manner. Bovine cumulus-oocyte complexes (COC) were aspirated from abattoir-derived ovaries and oocytectomized (OOX) by microsurgical removal of the oocyte. OOX were treated with doses of either denuded oocytes (DO) or various growth factors for 24 hours (± rFSH; 0.1 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
231
1
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(262 citation statements)
references
References 48 publications
11
231
1
12
Order By: Relevance
“…This may be due to timing of tissue analysis, the in vitro bias, and species differences. Interestingly, the expression of some proliferative genes was reported to be induced by the oocyte (Hussein et al 2005), and we can assume that it may compensate/counteract the early apoptosis signs. This survival behavior was also reinforced by the activation of cell morphology and cellular assembly functions.…”
Section: Cellular and Molecular Function Analysismentioning
confidence: 93%
“…This may be due to timing of tissue analysis, the in vitro bias, and species differences. Interestingly, the expression of some proliferative genes was reported to be induced by the oocyte (Hussein et al 2005), and we can assume that it may compensate/counteract the early apoptosis signs. This survival behavior was also reinforced by the activation of cell morphology and cellular assembly functions.…”
Section: Cellular and Molecular Function Analysismentioning
confidence: 93%
“…Recent studies have proven that oocytes may regulate the functions of cumulus itself instead of being controlled by cumulus (Gilchrist et al, 2008). Hussein et al(2005) demonstrated that soluble paracrine signals from the oocyte may contribute to the levels of apoptosis in cumulus cells rather than gap junctions, because destroying the gap junctions between cumulus cells and oocytes has effects on apoptosis in all cumulus cell layers instead of the closest layer to the oocyte. Growth-differentiation factor 9 (GDF9) and bone morphogenetic protein 15 (BMP15) are two key oocyte-secreted factors (OSFs), which are expressed in the ooplasm and function in cumulus cells.…”
Section: Interaction Between Ooplasmic Mitochondria and Cumulus Cellsmentioning
confidence: 99%
“…Oocytes define the cumulus cell phenotype by promoting glycolysis (Sugiura et al 2005), cholesterol synthesis (Su et al 2008), proliferation (Vanderhyden et al 1992, Gilchrist et al 2006, survival (Hussein et al 2005) and gene expression , while suppressing luteinization (Pincus & Enzmann 1935, Nekola & Nalbandov 1971 and opposing FSH-stimulated gene expression . The effects of oocytes on cumulus cells are mediated, in part, by factors such as GDF9 and BMP15, which activate the SMAD1/5/9 (Sugiura et al 2007) and SMAD2/3 signaling pathways.…”
Section: Introductionmentioning
confidence: 99%